PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SIFAT-SIFAT CAHAYA - Nurkhasanah, Nurkhasanah; Jayadinata, Asep Kurnia; Irawati, Riana (Jurnal Pena Ilmiah, 2017)
Based on obtained preliminary data in V class students SDN Cipameungpeuk, founding a problem in the learning process. Teacher doing a learning with using a conventional approach, so the students less motivation to follow the lesson. Coping effort that problem with apply a Contextual Teaching and Learning model of learning. Research focus on performance of teacher, students activity, learning outcomes, and fixed through classroom action research, by using Kemmis and Taggart design. Used a interview sheets as the instrument, teacher performance observation sheets, student activity observation sheets, field notes, and test student learning outcomes. This research finished by III cycle. Planning cycle I88,89%, cycle II 94,44%, and cycle III 100%.Â Implementation cycle I 80,56%, cycle II 88,89%,andÂ cycle III 100%. Students activity cycle I 70,04%, cycle II 81,64%, and cycle III 87,92%. Students learning outcomes cycle I 52,17%, cycle II 78,27%, and cycle III 91,3%. Based on the obtained data, CTL model of learning can improve studentss learning outcomes.